2014
DOI: 10.1371/journal.pone.0084424
|View full text |Cite
|
Sign up to set email alerts
|

Physician Presence in an Ambulance Car Is Associated with Increased Survival in Out-of-Hospital Cardiac Arrest: A Prospective Cohort Analysis

Abstract: The presence of a physician seems to be beneficial for pre-hospital cardiopulmonary resuscitation (CPR) of patients with out-of-hospital cardiac arrest. However, the effectiveness of a physician's presence during CPR before hospital arrival has not been established. We conducted a prospective, non-randomized, observational study using national data from out-of-hospital cardiac arrests between 2005 and 2010 in Japan. We performed a propensity analysis and examined the association between a physician's presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 34 publications
(49 reference statements)
1
40
0
Order By: Relevance
“…In many parts of the world, ALS ambulances are also staffed with a physician specialist in emergency medicine. One study that used propensity analysis documented that the presence of a physician on the ambulance was associated with better short-and long-term outcome after OHCA [31], but other studies have failed to show benefit for prehospital physicians [32]. The findings of a recent systematic review were consistent with this benefit and suggested that physician-guided resuscitation may improve survival outcomes after OHCA [33], but the cost-effectiveness of this policy is controversial.…”
Section: Variations In Emergency Medical Services Systemsmentioning
confidence: 99%
“…In many parts of the world, ALS ambulances are also staffed with a physician specialist in emergency medicine. One study that used propensity analysis documented that the presence of a physician on the ambulance was associated with better short-and long-term outcome after OHCA [31], but other studies have failed to show benefit for prehospital physicians [32]. The findings of a recent systematic review were consistent with this benefit and suggested that physician-guided resuscitation may improve survival outcomes after OHCA [33], but the cost-effectiveness of this policy is controversial.…”
Section: Variations In Emergency Medical Services Systemsmentioning
confidence: 99%
“…Of 175,912 bystander-witnessed OHCA patients transported to hospital, any physician involvement in the prehospital setting was recorded in 30,619 and unknown in 86. We first excluded these cases because CPR quality and OHCA outcomes is reported to be affected by physician involvement [12,13]. The bystander-patient relationship was unknown in 160, DA-CPR instruction and/or CPR type (chest compression-only or conventional) were unknown in 2,751, and other fundamental data for time factors and/or survival were unknown in 3,031.…”
Section: Data Selectionmentioning
confidence: 99%
“…The disadvantages of using this outcome are the resources required to record it as well as loss of patients to follow up. In addition, patients with long term survival will have spent minutes in the EMS, followed by days in hospital, which raises the issue of differences in hospital treatment confounding results [33, 34]. As a pragmatic approach, we chose survival to hospital discharge as the primary outcome, and survival to hospital admission as a secondary outcome.…”
Section: Discussionmentioning
confidence: 99%